2005
DOI: 10.1002/jbm.b.30470
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue debonding of the roughened stem–cement interface: Effects of surface roughness and stem heating conditions

Abstract: The aim of this study was to determine the effects of cyclic loading on the debond process of a roughened stem-cement interface used in total hip arthroplasty. The specific goals were to assess the effects of two surgeon-controlled variables (stem heating and degree of stem surface roughness) and to determine if an independent finite element-based fracture mechanics model could be used to predict the debond response. A clamped cantilever beam geometry was used to determine the fatigue debond response of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…21 The reversed curing from the stem towards the bone eliminates the porosities induced by shrinkage at the stem-cement interface. 17,24 Our study confirms that the highest reduction in porosity at the stem-cement interface can be obtained when the stem is pre-heated and that vacuum mixing used alone is less effective.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…21 The reversed curing from the stem towards the bone eliminates the porosities induced by shrinkage at the stem-cement interface. 17,24 Our study confirms that the highest reduction in porosity at the stem-cement interface can be obtained when the stem is pre-heated and that vacuum mixing used alone is less effective.…”
Section: Discussionsupporting
confidence: 88%
“…Great efforts have been made to optimise cement formulation, [11][12] to improve mixing and/or injection, [13][14][15] and to select the best texture for the surface of the implant. 16,17 Despite these efforts, some degree of porosity can still be observed in bone cement mantles. [18][19][20] It has been suggested that porosity can be reduced by thermally influencing the rate of polymerisation of cement by preheating the stem before its insertion into the medullary canal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During this complex phenomenon, porosity and stresses at both interfaces and inside bulk cement are observed (Ahmed et al, 1982a;Bishop et al, 1996;Gilbert et al, 2000;Mann et al, 2007;Nuñ o and Amabili, 2002). Numerous studies (Bishop et al, 1996;Damron et al, 2006;Iesaka et al, 2003;Wang et al, 2003) have shown significant reduction of stem-cement interfacial porosity by stem pre-heating. Mann et al (2007) have shown that porosity at the stem-cement interface directly affects stem migration, and is thought to induce implant loosening.…”
Section: Introductionmentioning
confidence: 91%
“…Damron et al (2006) use the aluminum mold with surface asperities to represent trabecular bone, which allows interlocking between the cement and cortical wall. In the present study, the aluminum mold is polished to avoid interlocking between cement and bone and refers to no adhesion at this interface.…”
Section: Adhesion At the Cement-bone Interfacementioning
confidence: 99%